(untitled) (Perner’s Contacts, 2020)
The paper deals with solution of an issue of parking in cities. Specifically, it is focused on parking in residential city areas. The lack of parking places is a serious problem here and for that reason, cars are parked often in an inappropriate way. The paper presents specific proposals for supplementing of certified Methodology for preparation of sustainable urban mobility plans of cities in the Czech Republic in the field of parking. It proposes specific technological procedure of solution of parking in a residential area by application of a system approach. Basic inputs for solution of this parking are determined. Possible proposals of changes in parking are delimited. Authors at the Dubina housing estate in Pardubice performed application of selected proposals for changes.